A role for LHC1 in higher order structure and complement binding of the Cryptococcus neoformans capsule. - Yoon-Dong Park (Public Library of Science (PLoS), 2014)
Polysaccharide capsules are important virulence factors for many microbial pathogens including the opportunistic fungus Cryptococcus neoformans. In the present study, we demonstrate an unusual role for a secreted lactonohydrolase of C. neoformans, LHC1 in capsular higher order structure. Analysis of extracted capsular polysaccharide from wild-type and lhc1Δ strains by dynamic and static light scattering suggested a role for the LHC1 locus in altering the capsular polysaccharide, both reducing dimensions and altering its branching, density and solvation. These changes in the capsular structure resulted in LHC1-dependent alterations of antibody binding patterns, reductions in human and mouse complement binding and phagocytosis by the macrophage-like cell line J774, as well as increased virulence in mice. These findings identify a unique molecular mechanism for tertiary structural changes in a microbial capsule, facilitating immune evasion and virulence of a fungal pathogen.